“Work ethic” value as soeharto’s development tool in Indonesia - Jaes, Lutfan; Latiff, Azmi Abdul; Ismail, Fadillah; Damin, Zahrul Akmal; Ani, Fauziah; Abdul Aziz, Abdul Rahman (Science Publishing Corporation, 2018)
This research paper mainly discusses Soeharto and his “Work Ethic” value system. It focuses on the role of local wisdom as a fundamen-tal value that has moulded leadership character and style of Soeharto in Indonesia. A term during his leadership tenure was used by Soeharto to identify, list and explain the source of the dominant local wisdom. Content analysis was used as the method of analysis in to explain a series of “End of the Year Speech”, “Nationhood Speech” and “Party Speech”. Initial analysis on the speech texts showed that emphasis on values was given at every serie of the speeches delivered. Next, quotations of every paragraph in the speech texts were scru-tinized for groupings of dimensions (Value Dimensions) specifically referring to Asian Values. The paragraphs of every text were recited for the final time in order to identify Derived Values originated from each of the Value Dimensions. Recordings of data were carried out by using Archive for Technology, the Life World and Everyday Language. Text Interpretation (ATLAS).ti version 7 software. It was discovered that Soeharto used his “Nationhood Speech” serie as his main medium to deliver values to his people. Value Dimension “Work Ethics” was identified as the second most important value in his delivery of messages on development. Meanwhile, Derived Val-ues “Strong/Kind/Dilligent/Viable/Earnest” were values that frequently appeared in the dimension. At the end of this paper, an explana-tion on the application of these values in the leadership and development under Soeharto is obtained. In conclusion, a leader who manip-ulated local wisdom is capable of achieving development that is more pragmatic and effective. Reinvigorating the local wisdom is a sig-nificant factor that can catalyze a continuous development specifically in Indonesia and generally in the South East Asia.